Liability without Fault – an Exception to the General Rule of Private Law - Kochashvili, Ketevan (Journal of Law, 2023)
The principle of Fault liability is a general rule for the substantive branch of private law - civil law, and liability without fault - the so-called Strict liability, as it is referred to in Anglo-American law, is an exception to this rule. Both the provisions of the national and unified law provide for the exemption of releasing the participant in civil circulation from liability due to natural or social circumstances because it would have been impossible to have foreseen or avoided the incident if he had shown the necessary foresight and diligence because of the extraordinary and insurmountable nature of this circumstance. It should be noted that such circumstances in the scope of liability without fault cannot ensure the release of a person from responsibility. A creditor participating in a legal relationship, in the event of a delay in receiving performance, or a debtor because of exceeding the deadline to fulfill the obligation, regardless of their fault, bears the risk of performance of the obligation. Also, the owner of the source of increased danger is responsible for the damage caused to another person by the object or activity considered as a source of danger, regardless of his fault. Civil liability insurance is considered as a deterrent to no-fault liability, regarded as an injustice allowed by law. On the one hand, it socializes the risk for the person liable for the damage, on the other hand, it is found as a means of balancing the interests of the victim.